Lymphocytic myocarditis: a genetically predisposed disease?. (25th November 2020) - Artico, J; Merlo, M; Delcaro, G; Cannata, A; Gentile, P; De Angelis, G; Paldino, A; Bussani, R; Dal Ferro, M; Sinagra, G
Abstract: Background: Clinical presentation of myocarditis is extremely heterogeneous from asymptomatic to overt severe heart failure (HF). A complex interaction between pre-existing genetic background and inflammation might be responsible for this heterogeneity. Purpose: The aim of the present study was to investigate whether positive genetic background for pathogenic cardiomyopathy-related variants might underlie a higher susceptibility to left ventricular dysfunction in patients with active lymphocytic myocarditis. Methods: We prospectively performed genetic tests in 36 patients (46±15 years; 61% males; no relatives included) with biopsy-proven active lymphocytic myocarditis according to Dallas criteria and immunohistochemistry. Only pathogenic (P) or likely pathogenic (LP) variants were considered. Results: After genetic test, 31% of patients (n=11) were carriers of P/LP truncating variants in structural Cardiomyopathy related genes: Titin (TTN, n=8, 73%), Desmoplakin (DSP, n=1), Filamin C (FLNC, n=1) and RNA binding protein 20 (RBM20, n=1). Among the 27 patients presenting with HF and LV dysfunction, the positive genetic yield was similar to the total cohort (n=9, 34%; 90% with TTN). Two out of six arrhythmic patients (30%) were carriers in arrhythmogenic genes (i.e. DSP and FLNC), whereas no patients with infarct-like presentation were carriers. During follow-up, 44% of patients (n=16) presented normal Left Ventricular Ejection Fraction (LVEF). Carriers had a lower rate of LVEF normalization compared to non-carriers (18% vs 56%, respectively; p=0.035). Conclusion: Positive genetic testing for cardiomyopathy-related-genes might be found in a non-negligible percentage of patients with biopsy-proven myocarditis, especially if presenting with heart failure and LV dysfunction. Compared to non-carriers, carriers of P/LP variants show lower likelihood of LVEF normalization during follow-up. Funding Acknowledgement: Type of funding source: None